2003
DOI: 10.1002/uog.179
|View full text |Cite
|
Sign up to set email alerts
|

Peri‐ and intraventricular cerebral sonography in second‐ and third‐trimester high‐risk fetuses: a comparison with neonatal ultrasound and relation to neurological development

Abstract: Objectives To determine whether periventricular leukomalacia (PVL) and peri-and intraventricular hemorrhages can be detected in fetuses at risk for preterm birth and to establish the clinical significance of this finding. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 41 publications
2
25
0
Order By: Relevance
“…The first examined periventricular densities in 26 fetuses exposed to uteroplacental insufficiency before and after birth, with neurological follow-up until 24 months. 5 Grade-1A periventricular echodensities (white matter as bright or almost as bright as the choroid plexus) was seen in four fetuses. These densities were also seen within 24 h after birth.…”
Section: Transient Changes or Permanent Damagementioning
confidence: 92%
See 4 more Smart Citations
“…The first examined periventricular densities in 26 fetuses exposed to uteroplacental insufficiency before and after birth, with neurological follow-up until 24 months. 5 Grade-1A periventricular echodensities (white matter as bright or almost as bright as the choroid plexus) was seen in four fetuses. These densities were also seen within 24 h after birth.…”
Section: Transient Changes or Permanent Damagementioning
confidence: 92%
“…5,6 It has been demonstrated that the localization of the HII damage is age-dependent and widespread in neonates 2 :…”
Section: Age-related Predilection Areasmentioning
confidence: 99%
See 3 more Smart Citations